Sodium ion battery positive electrode material and preparation method and application thereof
By using high -temperature solid phases in the preparation of sodium ion battery positive materials and introducing mature chemical steps, the problem of poor circulation stability of the positive electrode material of laminate oxide sodium ion battery, and realized the improvement of high -capacity maintenance rate and magnification performance, which is suitable Industrial production.
Patent Information
- Application Number
- CN202411634798.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-15
Smart Images

Figure CN119153683B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion positive electrode materials, and in particular relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] The environmental pollution problem caused by excessive use of traditional fossil energy is becoming increasingly serious. This problem can be effectively alleviated by developing green renewable energy and seeking low-cost, large-scale energy storage systems. Lithium-ion batteries (LIBs) gradually began to be commercialized in the early 1990s. Due to their excellent energy density, they dominate the energy storage industry. However, lithium ore reserves are low and unevenly distributed, and with the continuous development of emerging industries such as electric vehicles, the demand and price of lithium have increased sharply. Sodium-ion batteries (SIBs) are considered to be a low-cost electrochemical energy storage technology that may replace LIBs in the future due to the abundant content of sodium in the earth's crust. Therefore, they have received widespread attention. Among them, the research and development of high-energy-density and long-life cathode materials is one of the keys to the development of sodium-ion batteries. Layered oxide cathode materials have become a hot topic in the research of sodium ion battery cathodes due to their high theoretical energy density. At present, the mainstream layered oxide cathode materials are mainly O3 phase and P2 phase. The P2 type layered oxide cathode material has a faster sodium ion transport rate due to its special sodium ion coordination environment; while the initial Na content of the O3 type layered oxide cathode material is relatively high, so after assembling into a full battery, the capacity of the cathode prepared by the O3 type layered oxide cathode material will be better than that of P2. However, layered oxide cathode materials are prone to irreversible phase changes in the high voltage range (under deep discharge state), such as P2-O2 phase change, which leads to irreversible structural changes and crystal dislocation accumulation of the electrode material during the charge and discharge process, causing rapid attenuation of the battery capacity and shortening the cycle life of the battery. At present, the common preparation and synthesis methods of layered oxide cathode materials are high temperature solid phase method and sol-gel method. The material obtained by the high-temperature solid phase method has a larger particle size and better crystallinity; while the material prepared by the sol-gel method has a more concentrated particle size distribution and has a higher reversible specific capacity and rate performance. For the same positive electrode material, the positive electrode material prepared by the high-temperature solid phase method has poor cycle stability, while the positive electrode material prepared by the sol-gel method has relatively excellent cycle performance. However, the sol-gel process is relatively cumbersome and requires a large amount of organic raw materials, which is not suitable for industrial production.
[0003] The patent with publication number CN 118073552 A discloses a P2 phase layered manganese-based positive electrode material prepared by a sol-gel method. The metal Bi and Ni doped P2 phase manganese-based positive electrode material is prepared by the sol-gel method. At a current density of 0.2C, its initial capacity is 128.73 mAh / g, and the capacity decays to 83.88 mAh / g after 50 cycles. The cycle stability needs to be further improved, and the preparation and synthesis process is complicated. Summary of the invention
[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide a positive electrode material for a sodium ion battery.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned sodium ion battery positive electrode material.
[0006] Another object of the present invention is to provide an application of the above-mentioned sodium ion battery positive electrode material in a sodium ion battery.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A sodium ion battery positive electrode material, the general structural formula of which is Na 0.7 Ni 0.27 Mn 0.64 Li 0.027 Ti 0.036 Sn 0.027 O2.
[0009] The method for preparing the above-mentioned sodium ion battery positive electrode material comprises the following steps:
[0010] Step 1, mixing a Na source, a Ni source, a Mn source, a Li source, a Ti source and a Sn source until uniform, to obtain a first substance, wherein the ratio of Na in the Na source, Ni in the Ni source, Mn in the Mn source, Li in the Li source, Ti in the Ti source and Sn in the Sn source is 0.735:0.27:0.64:0.02835:0.036:0.027 in terms of the amount of the substances;
[0011] In step 1, the Na source is Na2CO3 or NaOH.
[0012] In step 1, the Ni source is NiO.
[0013] In step 1, the Mn source is MnCO3 or MnO2.
[0014] In step 1, the Li source is Li2CO3 or LiOH.
[0015] In step 1, the Ti source is TiO2.
[0016] In step 1, the Sn source is SnO2.
[0017] In step 1, a Na source, a Ni source, a Mn source, a Li source, a Ti source and a Sn source are mixed and ball-milled until uniform to obtain the first substance.
[0018] Step 2, the first substance is placed in an air atmosphere at 800-1200 o C is sintered for 5 to 12 hours and cooled in the furnace to obtain the second material;
[0019] In step 2, heat up to 800~1200 o The rate of C is 1~5 o C / min.
[0020] Step 3, mixing the second substance with 50-100 o C of water and kept for 1 to 7 days (maturation), filtered, and dried to obtain a positive electrode material for a sodium ion battery. The ratio of the second substance to water is 1: (5 to 10) by weight.
[0021] In step 3, preferably at 60-70 o C is left for 1 to 7 days.
[0022] In step 3, the drying temperature is 50-200°C, and the drying time is 1-2 h.
[0023] The application of the above-mentioned sodium ion battery positive electrode material in sodium ion batteries to improve the capacity retention rate.
[0024] The application of the above-mentioned sodium ion battery positive electrode material in sodium ion batteries to improve the rate performance.
[0025] In the above technical solution, the sodium ion battery includes a liquid sodium ion battery and a solid sodium ion battery.
[0026] A sodium ion battery comprises the sodium ion battery positive electrode material.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The sodium ion battery of the present invention has excellent capacity retention, especially at high current density (above 0.5C current density), the capacity retention performance is significantly improved.
[0029] 2. The sodium ion battery of the present invention has excellent rate performance. After gradually increasing from 0.1C to 5C and then decreasing back to 0.1C, the discharge specific capacity of 0.1C before and after is almost the same, proving that it has excellent rate performance.
[0030] 3. The present invention adopts a high-temperature solid phase method and introduces a aging step to remove some sodium ions in the positive electrode material of the sodium ion battery and make its interlayer disordered, thereby improving the cycle stability of the sodium ion battery. The preparation method of the present invention is simple in process, environmentally friendly, and suitable for scale-up production. It has potential application value in the development of high-performance positive electrode materials for sodium ion batteries and solves the problem of poor cycle stability of layered oxide positive electrode materials for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Example 1;
[0032] Figure 2 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Example 2;
[0033] Figure 3 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Example 3;
[0034] Figure 4 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Example 4;
[0035] Figure 5 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Comparative Example 1;
[0036] Figure 6 The charge and discharge curve of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 1 at a current density of 0.2 C;
[0037] Figure 7 The charge and discharge curve of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 2 at a current density of 0.2 C;
[0038] Figure 8 The charge and discharge curve of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 3 at a current density of 0.2 C;
[0039] Fig. 9 The charge and discharge curve of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 4 at a current density of 0.2 C;
[0040] Fig.10 The charge and discharge curve of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 at a current density of 0.2 C;
[0041] Fig.11 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 1 at a current density of 0.2 C;
[0042] Fig.12 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 2 at a current density of 0.2 C;
[0043] Fig.13 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 3 at a current density of 0.2 C;
[0044] Fig.14 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 4 at a current density of 0.2 C;
[0045] Fig.15 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 at a current density of 0.2 C;
[0046] Fig.16 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 1 at a current density of 0.5 C;
[0047] Fig.17 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 2 at a current density of 0.5 C;
[0048] Fig.18 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 3 at a current density of 0.5 C;
[0049] Fig.19 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 at a current density of 0.5 C;
[0050] Fig. 20 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 1 at a current density of 1 C;
[0051] Fig.21 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 2 at a current density of 1 C;
[0052] Fig. 22 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 3 at a current density of 1 C;
[0053] Fig.23 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 4 at a current density of 1 C;
[0054] Fig.24The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 at a current density of 1 C;
[0055] Fig.25 The rate diagram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 1 at different current densities;
[0056] Fig.26 The rate diagram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 2 at different current densities;
[0057] Fig. 27 The rate diagram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 3 at different current densities;
[0058] Fig.28 The rate diagram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 1 at different current densities;
[0059] Fig.29 This is a SEM image of the sodium ion battery positive electrode material prepared in Example 1;
[0060] Fig.30 This is a SEM image of the sodium ion battery positive electrode material prepared in Example 2;
[0061] Fig.31 This is a SEM image of the sodium ion battery positive electrode material prepared in Example 3;
[0062] Fig.32 This is a SEM image of the sodium ion battery positive electrode material prepared in Example 4;
[0063] Fig.33 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1;
[0064] Fig.34 The charge and discharge curve of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 2 at a current density of 0.2 C;
[0065] Fig.35 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 2 at a current density of 0.2 C;
[0066] Fig.36 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 2 at a current density of 0.5 C;
[0067] Fig.37 The cyclic voltammogram of the sodium ion battery prepared from the sodium ion battery positive electrode material of Comparative Example 2 at a current density of 1 C. DETAILED DESCRIPTION
[0068] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0069] The raw material information involved in the following examples is as follows:
[0070] Diaphragm: Whatman glass fiber diaphragm D1823-025;
[0071] Ethanol: purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd. with a purity of 99.7%.
[0072] Sodium source (Na2CO3) was purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd., and nickel source (NiO), Ti source (TiO2), Sn source (SnO2), manganese source (MnCO3) and lithium source (Li2CO3) were purchased from McLean Reagent.
[0073] XRD was measured by an X-ray diffractometer (ARL EQUINOX 3000, Thermo Fisher Scientific) at 40 kV and 40 mA in the 2θ range of 10 to 80°.
[0074] The constant current charge / discharge performance tests (cycle performance and rate performance) were performed by an automatic battery tester system (LandCT2001A, China) at a constant temperature of 25 °C and 2.0~4.3 V.
[0075] 1C=150 mA g -1 .
[0076] Embodiment 1~4
[0077] A sodium ion battery positive electrode material (Na 0.7 Ni 0.27 Mn 0.64 Li 0.027 Ti 0.036 Sn 0.027 O2) preparation method, comprising the following steps:
[0078] Step 1, mixing a Na source, a Ni source, a Mn source, a Li source, a Ti source and a Sn source, and subjecting the mixture to high-energy ball milling for 2 h until the mixture is uniform (the ball milling medium is acetone), to obtain a first substance, wherein the ratio of Na in the Na source, Ni in the Ni source, Mn in the Mn source, Li in the Li source, Ti in the Ti source and Sn in the Sn source is 0.735:0.27:0.64:0.02835:0.036:0.027, the Na source is Na2CO3, the Ni source is NiO, the Mn source is MnCO3, the Li source is Li2CO3, the Ti source is TiO2, and the Sn source is SnO2;
[0079] Step 2, placing the first material in a muffle furnace under air atmosphere at 5 o C / min and the temperature was raised to 900 o C and in 900 o C is sintered for 12 h, and then naturally cooled to room temperature (20-25°C) to obtain the second substance;
[0080] Step 3, placing the second substance in A o C in deionized water and kept for B days (maturation), filtered, and heated at 200 o C was dried for 2 hours to obtain a positive electrode material for a sodium ion battery, wherein the ratio of the second substance to deionized water was 1:5 by weight. The values of A and B are shown in Table 1.
[0081] Table 1
[0082] Example <![CDATA[A( o C)]]> B (day) Example 1 60 1 Example 2 60 3 Example 3 60 7 Example 4 80 7
[0083] Comparative Example 1
[0084] A sodium ion battery positive electrode material, which is the second substance of embodiment 1.
[0085] Comparative Example 2
[0086] A sodium ion battery positive electrode material (Na 0.7 Ni 0.27 Mn 0.64 Li 0.027 Ti 0.036 Sn 0.027 O2), the preparation method is basically the same as that of Example 3, except that "deionized water" is replaced by "ethanol". The ratio of the second substance to ethanol is 1:5 by mass.
[0087] Examples 5-8 and Comparative Examples 3-4
[0088] A sodium ion battery (button-type half-cell, the diameter of the sodium ion battery is 20 mm, the thickness of the sodium ion battery is 3.2 mm), including: a positive electrode (working electrode), a counter electrode, a reference electrode, a diaphragm and an electrolyte, the counter electrode and the reference electrode are metal sodium sheets, the electrolyte in the electrolyte is NaClO4, and the concentration of the electrolyte in the electrolyte is 1 mol L -1The solvent in the electrolyte is a mixture of propylene carbonate (PC) and fluoroethylene carbonate (FEC), and the ratio of propylene carbonate (PC) to fluoroethylene carbonate (FEC) is 95:5 by volume. The method for preparing the positive electrode is as follows: the positive electrode material, the binder solution and the conductive additive (acetylene black) are mixed until uniform to obtain a slurry, the slurry is coated on an aluminum foil, and dried in a vacuum drying oven at 80°C, and the dried electrode piece is cut into a disc with a diameter of 12 mm using a cutting machine as the positive electrode (the mass loading of the positive electrode material on the positive electrode is 0.9 mg cm -2 ), wherein the binder solution is a mixture of polyvinylidene fluoride (PVDF) and N-methylpyrrolidone, and the concentration of polyvinylidene fluoride in the binder solution is 20 mg mL -1 , the ratio of the positive electrode material, polyvinylidene fluoride and the conductive additive (acetylene black) in the binder solution is 8:1:1 by mass, and the positive electrode material is one of the positive electrode materials for sodium ion batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 2. The sodium ion battery was assembled in a circulating argon glove box with a moisture content of less than 0.01 ppm and an oxygen content of less than 0.01 ppm.
[0089] Table 2
[0090] Sodium-ion batteries Preparation of positive electrode materials for sodium ion batteries Example 5 Example 1 Example 6 Example 2 Example 7 Example 3 Example 8 Example 4 Comparative Example 3 Comparative Example 1 Comparative Example 4 Comparative Example 2
[0091] The sodium ion battery positive electrode materials prepared in Examples 1 to 4 and Comparative Example 1 were subjected to powder X-ray diffraction test to obtain Figure 1~Figure 5 It has a P2 phase layered structure.
[0092] The diffraction pattern of the sodium ion battery positive electrode material prepared in Example 1 is as follows Figure 1 As shown, it is proved that the sodium ion battery positive electrode material prepared in Example 1 has a P2 phase layered structure.
[0093] The diffraction pattern of the sodium ion battery positive electrode material prepared in Example 2 is as follows Figure 2 As shown, it is proved that the sodium ion battery positive electrode material prepared in Example 2 has a P2 phase layered structure.
[0094] The diffraction pattern of the sodium ion battery positive electrode material prepared in Example 3 is as follows Figure 3 As shown, it is proved that the sodium ion battery positive electrode material prepared in Example 3 has a P2 phase layered structure.
[0095] The diffraction pattern of the sodium ion battery positive electrode material prepared in Example 4 is as follows Figure 4 As shown, it is proved that the sodium ion battery positive electrode material prepared in Example 4 has a P2 phase layered structure.
[0096] The diffraction pattern of the sodium ion battery positive electrode material prepared in Comparative Example 1 is as follows Figure 5As shown, it is proved that the sodium ion battery positive electrode material prepared in Comparative Example 1 has a P2 phase layered structure.
[0097] The sodium ion battery positive electrode materials prepared in Examples 1 to 4 and Comparative Example 1 all have a P2 phase layered structure, proving that water aging has no effect on the structure.
[0098] Figure 6 The charge and discharge curve of the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 1 at a current density of 0.2 C is as follows: Figure 6 As shown, the charge and discharge curves are smooth, the charge specific capacity is 139 mAh / g, and the discharge specific capacity is 144 mAh / g.
[0099] Figure 7 The charge and discharge curve of the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 2 at a current density of 0.2 C is as follows Figure 7 As shown, the charge and discharge curves are smooth, the charge specific capacity is 136 mAh / g, and the discharge specific capacity is 142 mAh / g.
[0100] Figure 8 The charge and discharge curve of the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 3 at a current density of 0.2 C is as follows: Figure 8 As shown, the charge and discharge curves are smooth, the charge specific capacity is 138 mAh / g, and the discharge specific capacity is 144 mAh / g.
[0101] Fig. 9 The charge and discharge curve of the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 4 at a current density of 0.2 C is as follows: Fig. 9 As shown, the charge and discharge curves are smooth, the charge specific capacity is 110 mAh / g, and the discharge specific capacity is 117 mAh / g.
[0102] Fig.10 The charge and discharge curve of the sodium ion battery prepared by the sodium ion battery positive electrode material of Comparative Example 1 at a current density of 0.2 C is as follows: Fig.10 As shown, the charge and discharge curves are smooth, the charge specific capacity is 123 mAh / g, and the discharge specific capacity is 148 mAh / g.
[0103] Fig.34 The charge and discharge curve of the sodium ion battery prepared by the sodium ion battery positive electrode material of Comparative Example 2 at a current density of 0.2 C is as follows: Fig.34 As shown, the charge and discharge curves are smooth, the charge specific capacity is 156 mAh / g, and the discharge specific capacity is 145 mAh / g.
[0104] like Fig.11As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 1 has an initial discharge specific capacity of 144 mA h / g at a current density of 0.2 C, and a capacity retention rate of 75% after 100 cycles.
[0105] like Fig.12 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 2 has an initial discharge specific capacity of 142 mA h / g at a current density of 0.2 C, and a capacity retention rate of 75% after 100 cycles.
[0106] like Fig.13 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 3 has an initial discharge specific capacity of 144 mA h / g at a current density of 0.2 C, and a capacity retention rate of 74% after 100 cycles.
[0107] like Fig.14 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 4 has an initial discharge specific capacity of 117 mA h / g at a current density of 0.2 C, and a capacity retention rate of 75% after 100 cycles.
[0108] like Fig.15 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Comparative Example 1 has an initial discharge specific capacity of 148 mA h / g at a current density of 0.2 C, and a capacity retention rate of 77% after 100 cycles.
[0109] like Fig.35 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Comparative Example 2 has an initial discharge specific capacity of 145 mA h / g at a current density of 0.2 C, and a capacity retention rate of 53% after 100 cycles.
[0110] like Fig.16 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 1 has an initial discharge specific capacity of 134 mA h / g at a current density of 0.5 C, and a capacity retention rate of 87% after 100 cycles.
[0111] like Fig.17 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 2 has an initial discharge specific capacity of 137 mA h / g at a current density of 0.5 C, and a capacity retention rate of 86% after 100 cycles.
[0112] like Fig.18As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 3 has an initial discharge specific capacity of 135 mA h / g at a current density of 0.5 C, and a capacity retention rate of 87% after 100 cycles.
[0113] like Fig.19 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Comparative Example 1 has an initial discharge specific capacity of 138 mA h / g at a current density of 0.5 C, and a capacity retention rate of 76% after 100 cycles.
[0114] like Fig.36 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Comparative Example 2 has an initial discharge specific capacity of 136 mA h / g at a current density of 0.5 C, and a capacity retention rate of 72% after 100 cycles.
[0115] like Fig. 20 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 1 has an initial discharge specific capacity of 134 mAh / g at a current density of 1 C, and a capacity retention rate of 88% after 100 cycles.
[0116] like Fig.21 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 2 has an initial discharge specific capacity of 135 mA h / g at a current density of 1 C, and a capacity retention rate of 87% after 100 cycles.
[0117] like Fig. 22 As shown, the sodium ion battery prepared from the sodium ion battery positive electrode material of Example 3 has an initial discharge specific capacity of 137 mA h / g at a current density of 1 C, and a capacity retention rate of 89% after 100 cycles.
[0118] like Fig.23 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 4 has an initial discharge specific capacity of 104 mA h / g at a current density of 1 C, and a capacity retention rate of 86% after 100 cycles.
[0119] like Fig.24 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Comparative Example 1 has an initial discharge specific capacity of 136 mAh / g at a current density of 1 C, and a capacity retention rate of 80% after 100 cycles.
[0120] like Fig.37 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Comparative Example 2 has an initial discharge specific capacity of 131 mAh / g at a current density of 1 C, and a capacity retention rate of 71% after 100 cycles.
[0121] like Fig.25 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 1 has a discharge capacity of 149 mA h / g, 146 mA h / g, 133 mAh / g, 130 mA h / g, 119 mA h / g and 101 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When returning to 0.1C, the discharge capacity is 142 mA h / g.
[0122] like Fig.26 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 2 has a discharge capacity of 147 mA h / g, 150 mA h / g, 137 mAh / g, 128 mA h / g, 116 mA h / g and 100 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When returning to 0.1C, the discharge capacity is 141 mA h / g.
[0123] like Fig. 27 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Example 3 has a discharge capacity of 148 mA h / g, 151 mA h / g, 136 mAh / g, 127 mA h / g, 117 mA h / g and 102 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When returning to 0.1C, the discharge capacity is 140 mA h / g.
[0124] like Fig.28 As shown, the sodium ion battery prepared by the sodium ion battery positive electrode material of Comparative Example 1 has a discharge capacity of 149 mA h / g, 144 mA h / g, 136 mAh / g, 131 mA h / g, 119 mA h / g and 101 mA h / g at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. When returning to 0.1C, the discharge capacity is 134 mA h / g.
[0125] Fig.29 This is the SEM image of the sodium ion battery positive electrode material prepared in Example 1. Fig.30 This is the SEM image of the sodium ion battery positive electrode material prepared in Example 2. Fig.31 This is the SEM image of the sodium ion battery positive electrode material prepared in Example 3. Fig.32 This is the SEM image of the sodium ion battery positive electrode material prepared in Example 4. Fig.33This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1. Figure 29 to Figure 33 It can be seen that the residual alkali (Na compounds) on the surface of the sodium ion battery positive electrode material is significantly reduced after water aging, and its morphology does not change significantly.
[0126] Figure 20~Figure 24 The long cycle diagrams of the sodium ion batteries obtained by preparing the sodium ion battery positive electrode materials from Examples 1 to 4 and Comparative Example 1 at 2.0-4.3 V and 1 C are respectively, Fig.37 The long cycle diagram of the sodium ion battery obtained by preparing the sodium ion battery positive electrode material in Comparative Example 2 at 2.0-4.3 V and 1 C; Figure 20~Figure 24 and Fig.37 By comparison, it can be seen that the capacity retention rate of the sodium ion battery prepared by Examples 1 to 4 is significantly improved compared with the comparative example. The performance of the examples and comparative examples is summarized and analyzed in combination with Table 3, proving that the heat treatment aging step can significantly improve the cycle stability of the positive electrode material of the sodium ion battery.
[0127] Table 3
[0128]
[0129] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A sodium ion battery positive electrode material, characterized in that: Its general structural formula is Na 0.7 Ni 0.27 Mn 0.64 Li 0.027 Ti 0.03 6Sn 0.027 O2, the capacity retention rate of the sodium ion battery prepared by the sodium ion battery positive electrode material at a current density of 0.5 C reaches 87%, and the capacity retention rate of the sodium ion battery prepared by the sodium ion battery positive electrode material at a current density of 1 C reaches 89%, wherein the preparation method of the sodium ion battery positive electrode material comprises the following steps: Step 1, mixing a Na source, a Ni source, a Mn source, a Li source, a Ti source and a Sn source until uniform, to obtain a first substance, wherein the ratio of Na in the Na source, Ni in the Ni source, Mn in the Mn source, Li in the Li source, Ti in the Ti source and Sn in the Sn source is 0.735:0.27:0.64:0.02835:0.036:0.027 in terms of the amount of the substances; Step 2, the first substance is placed in an air atmosphere at 800-1200 o C is sintered for 5 to 12 hours and cooled in the furnace to obtain the second material; Step 3, mixing the second substance with 50-100 o C of water and kept for 1 to 7 days, filtered, and dried to obtain a positive electrode material for a sodium ion battery. The ratio of the second substance to water is 1: (5 to 10) by weight.
2. The sodium ion battery positive electrode material according to claim 1, characterized in that In step 1, a Na source, a Ni source, a Mn source, a Li source, a Ti source and a Sn source are mixed and ball-milled until uniform to obtain the first substance.
3. The sodium ion battery positive electrode material according to claim 1, characterized in that In step 2, heat up to 800~1200 o The rate of C is 1~5 o C / min.
4. Use of the sodium ion battery positive electrode material as claimed in claim 1 to improve the capacity retention rate in a sodium ion battery.
5. The use according to claim 4, characterized in that The capacity retention rate of sodium ion batteries is 86~89% after 100 cycles at a current density of 1 C.
6. The use according to claim 4, characterized in that: The capacity retention rate of sodium ion batteries is 86~87% after 100 cycles at a current density of 0.5 C.
7. Use of the sodium ion battery positive electrode material as claimed in claim 1 in sodium ion batteries to improve rate performance.
8. A sodium ion battery, comprising the sodium ion battery positive electrode material according to claim 1.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN118073552A